Investigation on transport and thermal studies of solid polymer electrolyte based on carboxymethyl cellulose doped ammonium thiocyanate for potential application in electrochemical devices - Noor, NAM; Isa, MIN (Pergamon-Elsevier Science Ltd, 2024)
Indexed by WOS/ Scopus